Desenvolvimento de nanopartículas de PLGA encapsuladas com paclitaxel e funcionalizadas com bevacizumabe para terapia do carcinoma pulmonar - Martins, Beatriz Marchini Bindão (Universidade Federal de São Carlos, 2025)
Lung cancer is a highly prevalent and deadly malignant disease, ranking as the second most common type worldwide, according to the International Agency for Research on Cancer. Non-small cell lung cancer (NSCLC) accounts for approximately 85% of all diagnosed cases. Despite significant advancements in treatment over recent years, nanomedicine has emerged as a promising tool for exploring new therapeutic possibilities, offering alternatives to overcome the limitations of conventional treatments. This study aimed to develop and characterize a drug delivery system using PLGA nanoparticles functionalized with bevacizumab, a recombinant monoclonal antibody, to encapsulate and deliver paclitaxel. Paclitaxel is a chemotherapy drug widely regarded as one of the most significant breakthroughs in lung cancer treatment over the past two decades. Two synthesis methods—chemical and electrostatic—were tested to evaluate the efficiency of paclitaxel encapsulation and bevacizumab binding. The developed formulations were analyzed using physicochemical characterization techniques to compare the two synthesis methods and assess variations in drug and antibody concentrations. Results showed that nanoparticles synthesized using the chemical conjugation strategy, with a lower amount of antibody demonstrated greater stability. These nanoparticles had an average size of 261.35 nm, a polydispersity index (PDI) of 0.41, a zeta potential of -13.94 mV, a concentration of 1.07 × 10¹² particles/mL, and exceptionally high encapsulation and binding efficiencies—99.97% for paclitaxel and 99.94% for bevacizumab. Overall, this study highlights the potential of different nanoparticle formulation techniques to enhance precision in lung cancer treatment, offering a promising approach for future therapeutic applications.
Development of PLGA nanoparticles encapsulated with paclitaxel and functionalized with bevacizumab for lung carcinoma therapy.
Keywords: Nanopartículas de PLGA; Paclitaxel; Bevacizumabe; Carcinoma pulmonar; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS BIOLOGICAS::FARMACOLOGIA::ETNOFARMACOLOGIA